Functional Exhaustion of HBV-Specific CD8 T Cells Impedes PD-L1 Blockade Efficacy in Chronic HBV Infection - Ferrando-Martinez, Sara; Snell Bennett, Angie; Lino, Elisabete; Gehring, Adam J.; Feld, Jordan; Janssen, Harry L. A.; Robbins, Scott H. (Frontiers in Immunology, 2021)
Background: A functional cure for chronic HBV could be achieved by boosting HBV-specific immunity. In vitro studies show that immunotherapy could be an effective strategy. However, these studies include strategies to enrich HBV-specific CD8 T cells, which could alter the expression of the targets. Our aim was to determine the efficacy of anti-PD-L1 blockade ex vivo. Methods: HBV-specific CD8 T cells were characterized ex vivo by flow cytometry for the simultaneous analysis of six immune populations and 14 activating and inhibitory receptors. Ex vivo functionality was quantified by ELISpot and by combining peptide pool stimulation, dextramers and intracellular flow cytometry staining. Results: The functionality of HBV-specific CD8 T cells is associated with a higher frequency of cells with low exhaustion phenotype (LAG3-TIM3-PD-1+), independently of the clinical parameters. The accumulation of HBV-specific CD8 T cells with a functionally exhausted phenotype (LAG3+TIM3+PD-1+) is associated with lack of ex vivo functionality. PD-L1 blockade enhanced the HBV-specific CD8 T cell response only in patients with lower exhaustion levels, while response to PD-L1 blockade was abrogated in patients with higher frequencies of exhausted HBV-specific CD8 T cells. Conclusion: Higher levels of functionally exhausted HBV-specific CD8 T cells are associated with a lack of response that cannot be restored by blocking the PD-1:PD-L1 axis. This suggests that the clinical effectiveness of blocking the PD-1:PD-L1 axis as a monotherapy may be restricted. Combination strategies will likely be required to elicit a functional cure for patients with high levels of functionally exhausted HBV-specific CD8 T cells.